Analiza możliwości klas systemów inteligentnych do wspomagania kontrolingu banku komercyjnego - Palonka, Joanna (The Analysis of Intelligent System Classes Supporting Commercial Bank Controlling, 2006)
The article outlines the essence of controlling in a commercial bank and indicates ways in which controlling is supported by IT tools. The second part of the paper includes descriptions of expert systems, neural networks, hybrid systems and "intelligent assistants" which highly support controlling in commercial bank. The paper presents integrated Artificial Intelligence Software Package SPHINX, that can be used to built a controlling information system of a commercial bank.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 112-126